Financial, Non-Financial Indicators dan Corporate Governance terhadap Prediksi Financial Distress Perusahaan Sektor Transportasi - Dea Syifa; Wiwi Idawati (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Financial distress is a condition where the company experience a deteriorating stage of the financial situation before bankruptcy. This study aimed to prove the influence of financial, non-financial and corporate governance indicators on financial distress in transportation sector listed on the Indonesian Stock Exchange periods 2016-2020. This study used the Springate method (S-score) to measure the level of financial distress. The sample was obtained by purposive sampling method in obtain 21 companies in transportation sector. The data used is secondary data in the form of annual reports from the publication of Indonesia Stock Exchange. Data analysis technique used in this study is multiple linear analysis panel data which is processed using Eviews 10 software. The hypothesis is obtained from previous research and various theories from other sources. The results of this study indicate that interest coverage ratio has a positive influence on financial distress and going concern opinion has a negative influence on financial distress. Meanwhile, long-term debt to equity ratio, age of company, independent board of commissioners, and institutional ownership did not has a influence on financial distress.